Risk Factors Associated with Surgical Site Infection following Cesarean Section in Tertiary Care Hospital, Nepal - Astha Regmi; Neebha Ojha; Meeta Singh; Asmita Ghimire; Nisha Kharel (Hindawi Limited, 2022)
Background. Cesarean section (CS) is one of the most performed surgeries in obstetrics. Surgical site infection is the major cause of morbidity and mortality causing an increase in the duration of hospitalization as well as the cost of admission for the patient. Objective. To determine incidence of surgical site infection following cesarean section, classify them according to CDC criteria, and identify the different risk factors. Methodology. This is a case-control study conducted at the Department of Obstetrics and Gynecology at Tribhuvan University Teaching Hospital (TUTH), main campus of Institute of Medicine (IOM), Kathmandu, Nepal. Surgical site infections (SSI) in patients who underwent cesarean sections from February 2019 to August 2019 were taken as cases, while the patients who underwent cesarean section before or after the procedure and did not develop SSI comprised the controls. Visual inspection during ward rounds, reports from laboratory, and postprocedure follow-ups for up to 30 days formed the basis of identifying infections on the patients. Risk factors were identified by bivariate and multivariate logistic regression. Results. Out of 1135 cases of cesarean sections, 97 of them developed SSI with incidence rate of 8.54%. Among them, 94.85% were superficial incisional and 5.15% were deep incisional type of SSI with no organ space type. Cases had higher mean age 26.88±4.38 years compared to 24.81±5.08 years in controls. Host-related risk factors which led to higher odds of developing surgical site infection (SSI) were obesity with adjusted odds ratio (AOR) 15.72 (confidence interval (CI): 4.60-53.67), diabetes/hypertension in pregnancy with AOR 4.75(CI 1.69-13.32), and other medical diseases with AOR 9.38 (CI 2.89-30.46). Duration of the rupture of membrane for more than 18 hours with AOR 8.38 (CI 1.48-47.35), more than five per vaginal (PV) examination with AOR 1.93 (95% CI 1.03-3.64), and in labor status with AOR 6.52 (CI 1.17-36.38) were some procedure-related factors resulting into higher odds of infection. Conclusion. Multiple risk factors like age, obesity, medical complications during pregnancy, occurrence of labor status during cesarean section, prolonged duration of rupture of membrane for more than 18 hours, and more than five vaginal examinations before the procedure increases the chance of surgical site infection (SSI) following cesarean section.